2011
DOI: 10.1111/j.1532-849x.2011.00762.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Study of the Effect of Three Hydrogen Peroxide Concentrations on the Corrosion Behavior and Surface Topography of Alumina-Reinforced Dental Ceramic

Abstract: The amount of released ions is directly proportional to HP concentration and time of immersion. Specimens exposed to both HP and acetic acid showed increased weight loss and a higher corrosion rate than those exposed to acetic acid only. Surface roughness values were time and HP concentration dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Roughness studies involving immersion in dental bleaching agents and soft drinks have been performed only on dental enamel, composite resin, acrylic resin and other materials for dental restorations . These studies observed the values of the roughness profile (Ra) and surface characterization (SEM and AFM), concluding that the dental bleaching agents and cola soft drinks induced variations in the surface roughness of the dental materials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Roughness studies involving immersion in dental bleaching agents and soft drinks have been performed only on dental enamel, composite resin, acrylic resin and other materials for dental restorations . These studies observed the values of the roughness profile (Ra) and surface characterization (SEM and AFM), concluding that the dental bleaching agents and cola soft drinks induced variations in the surface roughness of the dental materials.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the dental bleaching agents, Turker and Biskin observed that 10 and 16% carbamide peroxide gels, which were applied to feldspathic porcelain over a period of 30 days, caused a decrease in the hardness, whereas the roughness increased significantly after the first 2 weeks of the application. Similarly, Abu‐Eittah and Mandour investigated the effect of 30, 35, and 38% hydrogen peroxide on the topography of a dental ceramic and observed by AFM and SEM analysis that the surfaces of all of the specimens had holes, with the 35 and 38% concentrations also exhibiting a significant change in the surface roughness. These results, although obtained for a ceramic substrate, are consistent with those obtained in this work because the Ti discs that were immersed in 35% hydrogen peroxide and 16% carbamide peroxide showed the largest changes in the surface roughness and in the SEM and AFM images compared with the other groups, which maintained characteristics and roughness values close to those of the initial period or control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One reason for this is that there might be an increase in release of free radicals from bleaching agents when the temperature rises, thus inducing greater effects on dental materials. 28 Also a previous study 29 presented that surface roughness of a ceramic material increased with increasing HP concentration. In this study the bleaching agents used are at high concentrations (35% and 46%).…”
Section: Discussionmentioning
confidence: 99%
“…28 After highly concentrated HP application (30%, 35%, 38%), the surface roughness of alumina-reinforced dental ceramic increased significantly with time of immersion as well as with the increase in concentration of HP. 29 The other investigation into the effects of 15% and 35% CP on the surface roughness and whiteness of overglazed and autoglazed low-fusing ceramic, reported that 1-week CP bleaching significantly affected the overglazed ceramic surface. 30 The increased roughness and whiteness of bleached ceramic were possibly due to the reduction of surface SiO 2 content.…”
Section: Dental Ceramicmentioning
confidence: 98%